Physiological Correlates to In-race Paratriathlon Cycling Performance - Stephenson, Ben Thomas; Shill, Alex; Lenton, John; Goosey-Tolfrey, Victoria (International Journal of Sports Medicine, 2020)
The purpose was to determine the physiological correlates to cycling performance within a competitive paratriathlon. Five wheelchair user and ten ambulant paratriathletes undertook laboratory-based testing to determine their: peak rate of oxygen uptake; blood lactate- and ventilatory-derived physiological thresholds; and, their maximal aerobic power. These variables were subsequently expressed in absolute (l∙min −1 or W), relative (ml∙kg−1∙min −1 or W∙kg −1) and scaled relative (or ml∙kg − 0.82 ∙min −1, ml∙kg − 0.32 ∙min −1 or W∙kg −0.32) terms. All athletes undertook a paratriathlon race with 20 km cycle. Pearson’s correlation test and linear regression analyses were produced between laboratory-derived variables and cycle performance to generate correlation coefficients (r), standard error of estimates and 95% confidence intervals. For wheelchair users, performance was most strongly correlated to relative aerobic lactate threshold (W∙kg −1) (r=−0.99; confidence intervals: −0.99 to −0.99; standard error of estimate=22 s). For ambulant paratriathletes, the greatest correlation was with maximal aerobic power (W∙kg −0.32) (r=−0.91; −0.99 to −0.69; standard error of estimate=88 s). Race-category-specificity exits regarding physiological correlates to cycling performance in a paratriathlon race with further differences between optimal scaling factors between paratriathletes. This suggests aerobic lactate threshold and maximal aerobic power are the pertinent variables to infer cycling performance for wheelchair users and ambulant paratriathletes, respectively.
Keywords: prediction; talent identification; monitoring; peak power output; triathlon; time trial